Actigraphic Sleep Pattern of Preschoolers With ADHD. Issue 4 (February 2020) - Melegari, Maria Grazia; Vittori, Elena; Mallia, Luca; Devoto, Alessandra; Lucidi, Fabio; Ferri, Raffaele; Bruni, Oliviero
Objective: To assess the features of sleep in preschoolers with ADHD by means of questionnaire and actigraphy.Method: Twenty-five ADHD and 21 age-matched typically developing (TD) preschool children underwent the Child Behavior Checklist (CBCL) for ages 1½ to 5 and Pre-School-Age Psychiatric Assessment interview. Sleep was assessed by means of a modified Sleep Disturbance Scale for Children and wrist actigraphy for at least 5 days.Results: Children with ADHD, compared with TD, showed higher scores in CBCL Withdrawal (58.83 vs. 51.15, p < .0001), Attention Problems (69.88 vs. 51.54, p < .0001), and Aggressive Behavior (59.46 vs. 51.08, p < .0001) dimensions; they also showed increased actigraphic nocturnal activity (activity index 31.57 vs. 25.74, p < .05); and night-to-night variability for sleep minutes (56.44 vs. 32.79, p < .01), mean wake episodes (1.34 vs. 0.98, p < .05), mean activity (2.64 vs. 1.71, p < .05), and activity index (5.15 vs. 3.77, p < .05).Conclusion: This pilot study in preschoolers with ADHD showed increased motor activity during sleep and night-to-night variability for sleep duration and motor activity.